Letter from Max Bredig to Harold C. Urey, February 8, 1947 - Bredig, Max Albert (1947)
Max Bredig (1902-1977) contributes $25.00 to help Karl Friedrich Bonhoeffer (1899-1957) recover from angina pectoris (chest pain). Bredig tells Harold C. Urey (1893-1981) that he will write to other colleagues who know Bonhoeffer in hopes they will help as well.
Keywords: Fajans, Kasimir, 1887-1975; Urey, Harold Clayton, 1893-1981; Bredig, Max Albert, 1902-1977; Bonhoeffer, Karl Friedrich, 1899-1957; War wounds; Fund raising